Theorising visual framing: contingency, materiality and ideology. Issue 1 (1st January 2020) - Bock, Mary Angela
Abstract : Visual framing is a popular paradigm for media research around the world but its conceptualisation remains vague and often neglects the richness of images. Just as with framing theory generally, its definition and operationalisation are matters of considerable debate. Visual framing's many applications may be advantageous for their bridging properties but at the same time demand theoretical refinement. Based on a review of 165 scholarly publications from the humanities and social sciences, this essay first argues that media research tends to emphasise literal depictions more than visual conventions or production, falling short of its interrogative and critical potential. The essay then proposes a model of visual framing that attends more carefully to the contingency and materiality of images in order to strengthen the paradigm's explanatory and critical value.